PROFIL KEMAMPUAN ANTARA KAPASITAS AEROBIK DAN ANAEROBIK PEMAIN SEPAK BOLA SMK 4 PEKANBARU - Bayu Kurniawan; Agus Sulastio; Alimandan , (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the extent of the ability profile between aerobic and anaerobic capacitors of SMK 4 Pekanbaru soccer players. The method used in the study is in the form of numbers and analysis using statistics. The population in this study were 18 SMK 4 Pekanbaru soccer players. In this study, sample increase was carried out using purposive sampling with a sample of 11 people. The instruments in this study used Multistage Fitness Test and Rast Test Then the data were analyzed using cross- respondent techniques. The results of this study show variations between individuals. The aerobic ability of the players is on average sufficient, namely 5 players or 45.45%. Meanwhile, the average anaerobic ability is at Very Good, namely 5 players or 45.45%). These data indicate that in general the anaerobic capacity in the team tends to be superior to its aerobic capacity. Z-score analysis shows a more specific physiological profile. Of the 11 players, 5 players (45.45%) had aerobic dominance as indicated by a positive Z- score difference, while 6 players (54.54%) had anaerobic dominance with a negative Z- score difference. Overall, this study confirms that the categories emerging from the test results provide an illustration that the team's aerobic capacity still needs to be improved because only 45.45% of players were in the Good or Very Good category, while the anaerobic ability of the majority was classified as Very Good (45.45%). Keywords: ability profile, between aerobic, anaerobic